Numerical investigation of an extra-deep drawing process with industrial parameters: formability analysis and process optimization (Fracture and Structural Integrity, 2024)
Extra-deep drawing is one of the most important sheet metal forming processes. The appearance of rupture and wrinkling are the most commonly encountered problems in this process. These defects are also very common at a local company, particularly in the manufacturing of wheelbarrow trays. As a consequence, substantial time and costs are incurred in industrial production. To thoroughly analyze and address these defects, the extra-deep drawing operation of the wheelbarrow tray was modeled by the FE method using Abaqus software. A defect-free manufactured wheelbarrow tray was used to validate the accuracy of the numerical approach. Precise measurements of its dimensions were taken through the reverse engineering process using a 3D scanner. Furthermore, other measurements were made with an ultrasonic thickness gauge to have more precise measurements of the product’s thickness. Comparing experimental and numerical results showed good agreement. The outcomes of the numerical analysis indicate that the final shape of the wheelbarrow tray does not contain rupture or wrinkling defects, accurately corresponding to the real cases manufactured at the company. Numerical modeling and optimization of the extra-deep drawing process performed in this study could potentially reduce production losses and improve the overall efficiency of industrial manufacturing.
Keywords: Extra-deep drawing; Experimental works; Numerical Analysis; Rupture; Wrinkling; Wheelbarrow tray